2013
DOI: 10.1002/jgt.21764
|View full text |Cite
|
Sign up to set email alerts
|

On Neighbor-Distinguishing Index of Planar Graphs

Abstract: A proper edge coloring of a graph G without isolated edges is neighbor‐distinguishing if any two adjacent vertices have distinct sets consisting of colors of their incident edges. The neighbor‐distinguishing index of G is the minimum number ndi(G) of colors in a neighbor‐distinguishing edge coloring of G. Zhang, Liu, and Wang in 2002 conjectured that ndi (G)≤Δ(G)+2 if G is a connected graph of order at least 6. In this article, the conjecture is verified for planar graphs with maximum degree at least 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
(10 reference statements)
0
15
0
Order By: Relevance
“… for bipartite graphs and for graphs of maximum degree 3, while Greenhill and Ruciński proved it for almost all 4‐regular graphs (asymptotically almost surely), see . Recently it was also verified for planar graphs of maximum degree Δ12 by means of the discharging method. Independently, Bonamy et al.…”
Section: Introductionmentioning
confidence: 94%
“… for bipartite graphs and for graphs of maximum degree 3, while Greenhill and Ruciński proved it for almost all 4‐regular graphs (asymptotically almost surely), see . Recently it was also verified for planar graphs of maximum degree Δ12 by means of the discharging method. Independently, Bonamy et al.…”
Section: Introductionmentioning
confidence: 94%
“…Recently Hornák et al [10] confirmed this conjecture for planar graphs with maximum degree at least 12. Balister et al [2] proved Conjecture 1.1 for graphs with ∆(G) = 3 and for bipartite graphs.…”
Section: Introductionmentioning
confidence: 54%
“…It was conjectured [27] that ′ a (G) ≤ Δ(G) + 2 for every connected graph G of order at least three different from the cycle C 5 . This was, for example, positively verified by Balister, Györi, Lehel, and Schelp [4] for bipartite graphs and for graphs of maximum degree 3, while Greenhill and Ruciński proved it asymptotically almost surely for random 4-regular graphs, see [10], and [12,13,25] for results concerning other particular graph classes. In general it is known that ′ a (G) ≤ 3Δ(G), [2], and ′ a (G) ≤ Δ(G) + O(log (G)), [4], for every graph G with no isolated edges.…”
Section: Introductionmentioning
confidence: 75%